Wireless sensor network-based solution for environmental monitoring: water quality assessment case study - Postolache, O. (2015)
The challenges of climate change, population growth, demographic change, urbanization and resource depletion mean that the world's great cities need to adapt to survive and thrive over the coming decades. Slashing greenhouse gas emissions to prevent catastrophic climate change, while maintaining or increasing quality of life, can be a costly and difficult process. Two factors that directly affect the life quality in the XXI century cities are the water and air quality that can be monitored using the combination of low cost sensing modules, machine to machine (M2M) and internet of things (IoT) technologies. In this context, this study presents a wireless sensor network architecture that combines low cost sensing nodes and a low cost multi-parameters sensing probe for reliable monitoring of water quality parameters of surface waters (lakes, estuaries and rivers) in urban areas. A particular attention is dedicated to the design of the conductivity, temperature and turbidity signal conditioning circuits, highlighting important issues related to linearisation, measuring dynamic range and low-cost implementation by using commercial off-the-shelf components and devices. Several issues related to the wireless sensor network implementation are included in this study, as well as several simulation and experimental results.